Who lived on the Swiss Plateau around 3300 BCE? Analyses of commingled human skeletal remains from the dolmen of Oberbipp. (29th July 2019) - Siebke, Inga; Steuri, Noah; Furtwängler, Anja; Ramstein, Marianne; Arenz, Gabriele; Hafner, Albert; Krause, Johannes; Lösch, Sandra
Abstract: Nowadays, the discovery and excavation of an almost intact Late Neolithic dolmen is rare, as those monuments were often visible in the landscape and have been investigated or destroyed in earlier times; therefore, information about the buried individuals has often been lost. The excavation of the dolmen, a stone grave chamber, from Oberbipp, Switzerland, in 2012 provided a unique opportunity to study human skeletal remains from a Late Neolithic collective burial (3350–2650 BCE). Over 2, 000 fragmented and commingled skeletal elements were recovered and form the basis of this morphological study. Established morphological methods were employed to evaluate the minimum number of individuals, age at death, sex, stature, and the presence of pathological alterations and trauma. Sex was determined additionally by aDNA analysis. Elements of the entire human skeleton were recovered indicating a primary burial site. At least 42 individuals ( femora ) from all age classes (57%:43% adults to subadults) were buried in the dolmen. Based on aDNA analysis ( n = 23, partes petrosae ) slightly more males than females (44%:35% males to females, 22% indeterminate) were recovered. Stature was estimated from complete femora ( n = 3) indicating an average body height between 154–157 cm. Pathological alterations and trauma could be observed on several bones, however, without indications for major interpersonal violence. The caries intensity of Swiss samples seems to be higher compared with other Neolithic European sites. A possible separation of burial areas for males and females based on the recovery of skeletal elements within the dolmen along with aDNA results is postulated. In addition, this article contributes to a better understanding of Late Neolithic populations in Central Europe.